ANALISIS KONDISI FISIK DOMINAN UNTUK MENINGKATKAN AGILITY DAN KEMAMPUAN LARI SPRINTER ATLET ACEH MENJELANG PON ACEH SUMUT - irfandi, fandy irfan (Sport Pedagogy Journal, 2023)
This study aims to obtain a number of information, understanding in order to improve the agility and dominant physical condition of Acehnese sprinters, especially ahead of the grand opening of the sports field. This type of research is descriptive evaluative, namely: a study that tries to describe various phenomena, events and events and symptoms that exist in the present. The research method used is the experimental method by performing agility abilities and physical condition abilities of sprinter athletes. The population in this study were 15 special athletes built ahead of PON. The sample was taken using random sampling technique which amounted to 10 people. Data collection techniques are carried out using three test items, namely: agility, leg muscle explosive power, speed, and 100 meter running ability. The results obtained in this study are tests and analyzes the ability of 100 meter runners PON running athletes, with an average score of 96.7 in the high (good) category with the following details: (1) as many as 10 respondents were in the high category with a percentage level of 90.12%, (2) as many as 6 respondents were in the medium category with a percentage level of 60.4%. Conclusion, thus the high ability to run the 100 meter distance of Aceh PON sprinters is at the level of agility and the dominant physical component of 100 meter runners, so overall it is in the very good category, with details: agility, leg muscle explosiveness of 100 meter runners of PON athletics is in the very good category, agility, speed of 100 meter runners, is in the very good category, the ability to run 100 meters of 100 meter runners can be said to be in the very good category and very ready to compete, especially at national scale events. So that it can be categorized as an agility category, the dominant physical condition of 100 meter runners PON athletics athletes is said to be in the very good category.